2022
DOI: 10.3389/fpubh.2022.833169
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-1 and HTLV-2 Infection Among Warao Indigenous Refugees in the Brazilian Amazon: Challenges for Public Health in Times of Increasing Migration

Abstract: IntroductionHuman T-lymphotropic virus (HTLV) infection is endemic in indigenous populations of the Americas. We describe herein the prevalence of HTLV-1 and HTLV-2 infection among Warao indigenous refugees from Venezuela living in Belém, Pará, Brazil.MethodsIn total, 101 individuals of both sexes (43 men and 58 women) between 18 and 77 years of age were investigated. Blood samples were collected and separated into plasma and leukocytes. Serological screening was performed using an enzyme-linked immunosorbent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The samples in this study can be identified by traces in red (PWUDs) and blue (their relatives). Oliveira-Filho et al, 2019a;de Souza et al, 2020;Ishak et al, 2020b), other Brazilian regions (Renner et al, 2006;Novoa et al, 2007;de Almeida Rego et al, 2010;de Oliveira et al, 2012;Magri et al, 2012;Pessôa et al, 2014;Bandeira et al, 2015Bandeira et al, , 2022Castro et al, 2018;Ribeiro et al, 2018), and in South American countries (Leon-Ponte et al, 1996;Miura et al, 1997;Talarmin et al, 1999;Berini et al, 2013;Abreu et al, 2022). However, the same viral subtype detected in 15 PWUDs was detected in their family members.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The samples in this study can be identified by traces in red (PWUDs) and blue (their relatives). Oliveira-Filho et al, 2019a;de Souza et al, 2020;Ishak et al, 2020b), other Brazilian regions (Renner et al, 2006;Novoa et al, 2007;de Almeida Rego et al, 2010;de Oliveira et al, 2012;Magri et al, 2012;Pessôa et al, 2014;Bandeira et al, 2015Bandeira et al, , 2022Castro et al, 2018;Ribeiro et al, 2018), and in South American countries (Leon-Ponte et al, 1996;Miura et al, 1997;Talarmin et al, 1999;Berini et al, 2013;Abreu et al, 2022). However, the same viral subtype detected in 15 PWUDs was detected in their family members.…”
Section: Discussionmentioning
confidence: 93%
“…HTLV-1a, HTLV-2b, and HTLV-2c have shown high frequencies in studies conducted in key populations in Brazil, such as prisoners, female sex workers (FSW), people who use illicit drugs (PWUDs), and men who have sex with men (MSM) (Castro et al, 2018;Oliveira-Filho et al, 2019a;de Souza et al, 2020;Bandeira et al, 2022). Recently, two epidemiological studies conducted with PWUDs, and indigenous refugees recorded the movement of people infected with HTLV-1 (1aB) and between Brazilian states and countries located in the Amazon region and evidenced the spread of these retroviruses in South America (Oliveira-Filho et al, 2019a;Abreu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, social, political, and economic crises have motivated intense migratory movements and refugee requests in Latin American countries, with an increasing number of Indigenous individuals living in public or self-managed shelters or even on the street in extreme poverty. These conditions represent an extra challenge to address, not only visual, but the general health care needs of such groups [68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…Despite sharing considerable structural homology and transmission routes with HTLV-1, human T-lymphotropic virus type 2 (HTLV-2) has a distinct geographic spread, with endemic regions in indigenous populations in the Americas and cohorts of intravenous drug users in the United States and Europe ( Khabbaz et al, 1992 ; Hall et al, 1996 ; Paiva and Casseb, 2015 ; Martinez et al, 2019 ; Ishak et al, 2020 ; Abreu et al, 2022 ). HTLV-2 has not been causally linked to hematologic disease, although cases of neurological pathologies have been proposed ( Hjelle et al, 1992 ; Jacobson et al, 1993 ).…”
Section: Introductionmentioning
confidence: 99%